2020
DOI: 10.13031/trans.13929
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Extension Methods in the U.S. to Promote Irrigation Water Management

Abstract: HIGHLIGHTSUniversity extension has been playing a larger role, serving a larger number of irrigated farms.Extension programs in irrigation water management (IWM) have been transitioning away from lectures and field tours as the primary means of knowledge transfer.New IWM programs focus on experiential learning, development of practitioner networks, and industry participation.Abstract. Promotion and adoption of irrigation water management (IWM) technology, tools, and best management practices are important as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Extension's inconsistent success in guiding growers to adopt more efficient irrigation practices could be explained in part by the delivery method used. Historically, Extension programs were delivered via lectures, field days, information sheets and demonstrations of a practice [26]. Following program delivery, the typical next step for growers once they have determined the benefits outweigh the costs of a given practice is conducting on-farm trials of that practice as a final evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Extension's inconsistent success in guiding growers to adopt more efficient irrigation practices could be explained in part by the delivery method used. Historically, Extension programs were delivered via lectures, field days, information sheets and demonstrations of a practice [26]. Following program delivery, the typical next step for growers once they have determined the benefits outweigh the costs of a given practice is conducting on-farm trials of that practice as a final evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Progress in irrigation scheduling in the U.S. was the topic of three Special Collection journal articles (Butts et al, 2020;King et al, 2020;Taghvaeian et al, 2020). The progression of Irrigator Pro, an irrigation scheduling decision support system (DSS), was discussed by Butts et al (2020).…”
Section: Irrigation Management (Strategies Scheduling and Modeling)mentioning
confidence: 99%
“…A review of agricultural irrigation scheduling progress within the last decade in the U.S., its current status, and its anticipated future was provided by Taghvaeian et al (2020). USDA-NASS survey data were used to illustrate that many irrigators continue to use qualitative measures to inform irrigation scheduling decisions, rather than quantitative, science-based tools.…”
Section: Irrigation Management (Strategies Scheduling and Modeling)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that low adoption occurs because farmers either lack information on costs and benefits or they do not have positive beliefs and attitudes towards their use of the technology (Cartwright et al, 2019;O'Shaughnessy et al, 2019). Researchers and irrigation industry recognize the complexity of implementing these practices and suggest fostering the creation of communities or peer-to-peer networks of producers to exchange knowledge and build skills (Rudnick et al, 2020), as well as training crop consultants and equipment dealers to help with implementation and troubleshooting (O'Shaughnessy et al, 2019). The group of scientists working on this study firmly believe that the adoption of precision irrigation strategies could increase if farmers are provided with information on implementation costs and benefits.…”
Section: Introductionmentioning
confidence: 99%